Comparing the effect of methanolic and aquatic extract of Callistemon viminalis (SOl. Ex Gaertn.) G. Don with amphotericin B and their synergistic effects - sayed jalal alladin ashraf mansuri; maryam ramezanian (Fasa University of Medical Sciences, 2017)
Background & Objective: The emergence of fungal drug-resistance and also different side- effects related to the currently available drugs has led to a high demand for novel antifungal drugs. The purpose of this study was to evaluate the inhibitory activity of methanolic and aquatic extracts of Callistemon viminalison on the growth of Candida albicans in vitro. Materials & Methods: Having dried the leaves, the researchers prepared the extracts by distillation using methanol and water. The minimum lethal activity of 500, 250 and 125 µg/ml concentrations of the extracts on the yeast C.albicans was tested using disk diffusion and dilution method. In order to study the synergistic effect, a standard strain of C. albicans was cultured on medium containing methanol extract and then amphotericin B discs were put on it. Results: Based on the results, the antifungal activity of Callistemon viminalis methanol extract on C.albicans was more than the aqueous extract. In considering the Minimum Inhibitory Concentration (MIC), the methanol extract of the Callistemon viminalis at a concentration of 62.5μg/ml and the aqueous extract at a concentration of 250μg/ml inhibitory effect on C. albicans. The inhibition zone diameter of amphotericin B was 18mm and should be combined with Callistemon viminalis methanol extract at a concentration of 62.5μg/ml was 21mm, and also in combination with the aqueous extract at a concentration 250μg/ml it was 19 mm. Conclusion: Although amphotericin B is the most effective drug for treating systemic fungal infections, its effect will increases when combined with Callistemon viminalis extracts.